PEMEROLEHAN KOSA KATA BAHASA INDONESIA ANAK USIA TIGA SAMPAI EMPAT TAHUN - Murnisma (JOEL: Journal of Educational and Language Research, 2021)
Vocabulary acquisition in children aged three to four years begins with the ability to pronounce a word, and develops into two, three, four words and so on, thus forming a simple sentence. This writing aims to examine the acquisition of Indonesian vocabulary for children aged three to four years. This research is qualitative research to obtain accurate data on the acquisition of Indonesian vocabulary for children aged three to four years that living in Bima complex, Lasinrang street, Paleteang district, Pinrang regency. The data collection in this research is library research and field research. The results of this research indicate that children aged three to four years often use nouns rather than verbs, adjectives, and adverbs. Acquisition of vocabulary with affix is still rarely spoken, while confixes and infixes have not been found